The Wright brothers - McCullough, David G. (Simon & Schuster, 2015)
"As he did so brilliantly in THE GREAT BRIDGE and THE PATH BETWEEN THE SEAS, David McCullough once again tells a dramatic story of people and technology, this time about the courageous brothers who taught the world how to fly, Wilbur and Orville Wright"--Provided by publisher.